Procedural and legal regime of legal activity: nature, essence, purpose - Valery P Belyaev; Galina S Belyaeva; Vladislav Yu Turanin; Tamila M Nincieva; Igor Y Karpov (Revista de Investigaciones Universidad del Quindío, 2022)
This article attempts to consider a number of controversial issues regarding the definition of the nature, essence (including the concept and signs) and the purpose of the procedural legal regime in the theory of procedural legal regulation. The procedural and legal regime, as an element of the procedural-legal form, unfortunately, has not received sufficient development in legal science; a gap, in particular, remains the issues of establishing the characteristics of the category under consideration, without which it is impossible to establish the nature, essence and purpose of the procedural and legal regime. This remark is also true in relation to the definition of the concept of a procedural and legal regime, since the approaches available in legal science, for the most part, do not reveal the features and unique legal nature of the category under study. The authors of the article, on the basis of establishing the essential features of the procedural and legal regime, proposed its authentic definition, as based on a certain combination of procedural and legal means and principles of a special procedure for procedural and legal regulation of activities of subjects and participants in the legal process, aimed at legal and reasonable consideration and resolution of legal cases.